Plyometric-Jump Training Effects on Physical Fitness and Sport-Specific Performance According to Maturity: A Systematic Review with Meta-analysis - Rodrigo Ramirez-Campillo; Andrew Sortwell; Jason Moran; José Afonso; Filipe Manuel Clemente; Rhodri S. Lloyd; Jon L. Oliver; Jason Pedley; Urs Granacher (SpringerOpen, 2023)
Abstract Background Among youth, plyometric-jump training (PJT) may provide a safe, accessible, and time-efficient training method. Less is known on PJT effectiveness according to the maturity status. Objective This systematic review with meta-analysis set out to analyse the body of peer-reviewed articles assessing the effects of PJT on measures of physical fitness [i.e., maximal dynamic strength; change of direction (COD) speed; linear sprint speed; horizontal and vertical jump performance; reactive strength index] and sport-specific performance (i.e., soccer ball kicking and dribbling velocity) according to the participants' maturity status. Methods Systematic searches were conducted in three electronic databases using the following inclusion criteria: (i) Population: healthy participants aged < 18 years; (ii) Intervention: PJT program including unilateral and/or bilateral jumps; (iii) Comparator: groups of different maturity status with control groups; (iv) Outcomes: at least one measure of physical fitness and/or sport-specific performance before and after PJT; (v) experimental design with an active or passive control group, and two or more maturity groups exposed to the same PJT. The DerSimonian and Laird random-effects models were used to compute the meta-analysis. The methodological quality of the studies was assessed using the PEDro checklist. GRADE was applied to assess certainty of evidence. Results From 11,028 initially identified studies across three electronic databases, 11 studies were finally eligible to be meta-analysed (n total = 744; seven studies recruited males; four studies recruited females). Three studies were rated as high quality (6 points), and eight studies were of moderate quality (5 points). Seven studies reported the maturity status using age at peak height velocity (PHV; pre-PHV values up to − 2.3; post-PHV up to 2.5). Another four studies used Tanner staging (from Tanner I to V). The training programmes ranged from 4 to 36 weeks, using 1-3 weekly training sessions. When compared to controls, pre-PHV and post-PHV participants obtained small-to-moderate improvements (ES = 0.35 − 0.80, all p < 0.05) in most outcomes (i.e., sport-specific performance; maximal dynamic strength; linear sprint; horizontal jump; reactive strength index) after PJT. The contrast of pre-PHV with post-PHV youth revealed that PJT was similarly effective in both maturity groups, in most outcome measures except for COD speed (in favour of pre-PHV). PJT induces similar physical fitness and sport-specific performance benefits in males and females, with a minimal exercise dosage of 4 weeks (8 intervention sessions), and 92 weekly jumps. Results of this meta-analysis are based on low study heterogeneity, and low to very low certainty of evidence (GRADE analysis) for all outcomes. Conclusion Compared to control participants, PJT resulted in improved maximal dynamic strength, linear sprint speed, horizontal jump performance, reactive strength index, and sport-specific performance (i.e., soccer ball kicking and dribbling velocity). These effects seem to occur independently of the maturity status, as both pre-PHV and post-PHV participants achieved similar improvements after PJT interventions for most outcomes. However, several methodological issues (e.g., low sample sizes and the pooling of maturity categories) preclude the attainment of more robust recommendations at the current time. To address this issue, consistency in maturity status reporting strategies must be improved in future studies with the general youth population and youth athletes.